Cognitive Processes in Worry and Paranoia: Investigation of the Looming Cognitive Style. Issue 4 (October 2013) - Clemente, Jacinta; Gleeson, John F.; Lim, Michelle H.
The present study investigated a cognitive vulnerability known as the Looming Cognitive Style (LCS), which has previously been associated with anxiety and worry but not depression, in a group of pathological worriers. The present study is the first to examine LCS in a group diagnosed with a psychotic disorder with a history of persecutory delusions. Twenty-five individuals assessed as pathological worriers and 24 individuals diagnosed with a psychotic disorder were included in the study. In the present study, 63 percent of the psychosis group met the criteria for pathological worry. While both groups did not significantly differ on mean levels of LCS, current findings add to growing empirical evidence that the LCS is a cognitive vulnerability specific to anxiety and suggest that the psychological processes underlying worry in individuals with anxiety are distinct from processes underlying worry in psychosis.